2010
DOI: 10.1051/0004-6361/200912183
|View full text |Cite
|
Sign up to set email alerts
|

The central star of the planetary nebula PB 8: a Wolf-Rayet-type wind of an unusual WN/WC chemical composition

Abstract: A considerable fraction of the central stars of planetary nebulae (CSPNe) are hydrogen-deficient. As a rule, these CSPNe exhibit a chemical composition of helium, carbon, and oxygen with the majority showing Wolf-Rayet-like emission line spectra. These stars are classified as CSPNe of a spectral type [WC]. We perform a spectral analysis of CSPN PB 8 with the Potsdam Wolf-Rayet (PoWR) models for expanding atmospheres. The source PB 8 displays wind-broadened emission lines from strong mass loss. Most strikingly,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 33 publications
6
69
0
Order By: Relevance
“…Prinja and Massa (2013) suggested that the ratio of 23 Or from the black troughs, if present 24 Sometimes, two velocity laws with different β are combined, e.g. Todt et al 2010 narrow features observed at terminal velocities in the UV resonance lines of B-supergiants provides a clumping independent tool to estimate mass-loss rates in these objects. This may be especially important because in B-type supergiants, the Hα line might be optically thick, and thus lose its diagnostic value (Petrov et al, 2014).…”
Section: Mass-loss Diagnostics and The Effects Of Wind Clumpingmentioning
confidence: 99%
“…Prinja and Massa (2013) suggested that the ratio of 23 Or from the black troughs, if present 24 Sometimes, two velocity laws with different β are combined, e.g. Todt et al 2010 narrow features observed at terminal velocities in the UV resonance lines of B-supergiants provides a clumping independent tool to estimate mass-loss rates in these objects. This may be especially important because in B-type supergiants, the Hα line might be optically thick, and thus lose its diagnostic value (Petrov et al, 2014).…”
Section: Mass-loss Diagnostics and The Effects Of Wind Clumpingmentioning
confidence: 99%
“…A spectral analysis based on a high resolution spectrum, Todt et al (2010) revealed that this object has a stellar temperature of about 50 kK and an unusual composition with He:H:C:N:O=55:40:1:1:1 by mass and resembles spectroscopically a massive WN/C star.…”
Section: Pbmentioning
confidence: 99%
“…The PoWR code has been used extensively to analyse not only massive stars with strong stellar winds (e.g. Liermann et al 2010), but also low‐mass central stars of planetary nebulae, and extreme helium stars (Hamann 2010; Todt et al 2010). The PoWR code solves the non‐LTE radiative transfer in a spherically expanding atmosphere simultaneously with the statistical equilibrium equations and accounts at the same time for energy conservation.…”
Section: Stellar Windsmentioning
confidence: 99%